Coastal water quality of Tioman island: effects of human activity and the distance from shoreline - Rahman, Mohammad Mustafizur; Mohammad Noor, Normawaty; Saad, Shahbudin; Yunus, Kamaruzzaman (2012)
A study was conducted to know the (i) effects of anthropogenic activity, and (ii) effects of distance from shoreline on the coastal water quality of Tioman Island. . This study was a part of marine expedition conducted on 4 July 2012 on coral diversity and distribution around coastal water of the Tioman Island. A series of physico-chemical parameters namely temperature, dissolved oxygen, pH, salinity, transparency, total suspended solids, nitrate, ammonia, phosphate phosphorus and silicate were determined in this study. A total of 16 different study sites (station 1-16) were selected in the coastal water around the Tioman Island. Half of the study sites were located within 1 km from shoreline and other half were located approximately 6 km away from shoreline. Some study sites are characterized by no human activity, while some are characterized by diving activities. A few study sites are characterized with both diving activity and near residential area. The overall mean values of different water quality parameters recorded in the all sampling stations were temperature 27.98  0.40oC, pH 8.34  0.02, dissolved oxygen 6.92  0.43 (mg/l), salinity 33.54  0.11 pss, TSS 0.39  0.03 g/L, nitrate 0.85  0.55 µM, ammonia 1.89  0.56 µM, phosphate 0.16  0.09 µM, silicate 2.62  0.76 µM. Temperature, DO, transparency, salinity and ammonia were significantly affected by anthropogenic activity, while anthropogenic activity had no significant effects on pH, total suspended solids, nitrate and phosphate. No significant different was observed between the water quality of 1 km from shoreline and 6 km away from shoreline. Good and careful management by the authorities of this island may save the biodiversity and beauty of the coastal water of Tioman Island. Therefore, a balance between human activity and conservation of biodiversity on the coastal water of the Tioman Island is needed.